KECERDASAN EMOSI DAN PENYESUAIAN DIRI (Studi Aplikasi Kode Etik Mahasiswa di STAIN Padangsidimpuan) - Syafrida Siregar, Lis Yulianti (TAZKIR: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2018)
Background of this research is there some infraction in code of ethics which is done by students collage. It is about akhlaqulkarimahand is also about how to good wear as like as Islam that wear of students collage of Institute for Islamic Studies Padangsidimpuan. This case is a decadence of moral in circle of students collage. The purpose of this research is to know how the emotional intelligence and how students collage for adapting. This research was done in code of ethic application at studentsâ collage of IAIN. Then, to know the resistivity factor of students collage in applying of code of ethic, and how is to adapt as students collage of IAIN. Furthermore, this research is to know the effort that was done of deputy of IAIN Padangsidimpuan in motivating students collage for doing the code of ethic IAIN Padangsidimpuan. Based on the data analysis, the researcher used descriptive qualitative method. This research was done to observe phenomena with scientific logic. Based on method, this research was phenomenological descriptive. It means that, this research was also to describe the true condition that had happened in field as natural. The result of this research showed that emotional intelligence and students adaptation was related with code of ethic IAIN Padangsidimpuan which was less. Moreover, still found some infraction in code of ethic. For this case, guidance and construction is needed for attitude of students collage in IAIN Padangsidimpuan.